Numerical Analysis of Structural Performance of Concrete-GFRP Composite I-Beam - Chen, Zhaohui; Xing, Jiajie; Luo, Qiwen; Zhang, Xiaoyue (Frontiers in Materials, 2022)
The concrete-GFRP composite beams have received extensive attention in civil engineering. However, the ambiguity of the fracture, debonding of the interface, and the GFRP profile limit the precise design of the composite beam. This article presents a comprehensive numerical study for the structural performance of composite pultruded GFRP beams to provide a better understanding of the mechanism of interfacial debonding and GFRP matrix fracture. The failure and delamination process of pultruded GFRP for anisotropy of materials is modeled using the Hashin criteria. The bond–slip behavior between the concrete slab and the top flange of the GFRP I-beam is simulated by the bilinear cohesive interface element. The availability and accuracy of the finite element model are verified by comparison with the four-point bending test results of the pure GFRP I-beam and composite beams as well. Based on the proposed comprehensive finite element model, the effects of the strength, thickness, and width of the concrete slab and the shear-span ratio of the beam on the structural behavior of the composite beam are studied. According to the parametric analysis, the excessive high strength of concrete, the width, and/or thickness of the concrete slab would lead to shear failure of the slab rather than significantly increasing the ultimate load of the composite beam. When having a small shear-span ratio, the matrix fracture and delamination will occur in the web of the GFRP profile. In addition, the height of the I-profile web has a significant effect on the stress and strain distribution of the composite beam. These parametric analyses could provide the numerical basis for the design of the GFRP composite beams.